SPIRITUAL VALUE OF ALTHUSSER AND IDEOLOGICAL GRAMSCY HEGEMONY ANALYSIS - Ghazalba, Muhammad Ahsana (HUMANIKA, 2020)
This study is a literature that is entirely derived from written sources. Sholawat or Singir become the object of research material, The focus of this study is the spiritual values and the ideology contained in sholawat, analysis using the theoryAlthusser and Gramsci's ideological hegemony, Ideology contained in shoalawat namely 1)persuasive,2) Identity, 3) Reward and 4) Punishment, While the spiritual values that exist inside sholawat namely 1)To the praise of the Prophet Muhammad, 2) Birth of the Prophet SAW, 3) Phoenix Prophet Muhammad, 4) Glory Qur'an and praise for, 5) Ascension of the Prophet Muhammad, and 6) Tawassul To the Prophet Muhammad.